Physical Modeling of a Shallow-Buried Metro Tunnel in the Soft Loess Layer Using Similarity Theory - Xuemeng Jiang; Lele Hou; Shuping Shang; Longfei Xu; Hangfei Yu (Advances in Civil Engineering)
The special engineering characteristics of loess will inevitably bring hidden trouble to the construction of shallow buried subway tunnel. The purpose of this paper is to investigate the variation law of surrounding rock stress, lining stress, and surface settlement in loess tunnel construction and further explore the optimum construction method in the soft loess area. A model test considering the different excavation methods and prereinforcement measures was conducted to measure the surrounding rock pressure, lining stress, and surface settlement under different working conditions. The results show that the sequence of tunnel excavation had a great influence on the stability of the tunnel. As the experimental steps increased, the surrounding rock stress and lining stress at each monitoring section gradually increase. Especially, stress concentration could easily occur at the arch foot of the tunnel. The pre-reinforcement measure, especially the WSS grouting, was more crucial than the excavation method. Considering the number of elements, the combination of DSDM excavation method and WSS grouting reinforcement method was proposed as the final construction method of the tunnel in soft loess area in this paper. The research results can effectively guide the design and construction of a shallow tunnel in the soft loess area.